Methanolic Extract of Lysimachia Candida Lindl. Prevents High-Fat High-Fructose-Induced Fatty Liver in Rats: Understanding the Molecular Mechanism Through Untargeted Metabolomics Study - Kamboj, Parul; Sarkar, Soumalya; Gupta, Sonu Kumar; Bisht, Neema; Kumari, Deepika; Alam, Md. Jahangir; Barge, Sagar; Kashyap, Bhaswati; Deka, Barsha; Bharadwaj, Simanta; Rahman, Seydur; Dutta, Partha Pratim; et al. (Frontiers in Pharmacology, 2021)
Fatty liver is one of the most common metabolic syndrome affecting the global population. Presently, limited treatment modalities with symptomatic approach are available for alleviating fatty liver. Traditional and herbal treatment modalities have shown evidence to improve the disease pathology. In the present research work, evaluation of a selected medicinal plant Lysimachia candida Lindl. was carried out to investigate its beneficial effects on fatty liver disease in rats. Male Sprague Dawley (SD) rats were fed with high-fat high-fructose diet to induce fatty liver phenotypes. After induction for 15 weeks, methanolic extract of Lysimachia candida Lindl. (250 mg/kg b. w. p. o.) was administrated to the rats daily for the next 17 weeks. Blood samples were collected at different time points to analyze fasting blood glucose levels and relevant biochemical parameters important for the assessment of metabolic disease phenotypes. Liquid chromatography-mass spectrometry (LC-MS) based metabolomics was done to study the dynamics of metabolic changes in the serum during disease progression and how the medicinally important plant extract treatment reversed the metabolic diseases. Multivariate data analysis approaches have been employed to understand the metabolome changes and disease pathology. This study has identified the interplay of some metabolic pathways that alter the disease progression and their reversal after administration of the plant extract. Different group of metabolites mainly bile acids, fatty acids, carnitines, and their derivatives were found to be altered in the diseased rats. However, all the metabolites identified between control and disease groups are mainly related to lipid metabolism. The results depict that the treatment with the above-mentioned plant extract improves the regulation of aberrant lipid metabolism, and reverses the metabolic syndrome phenotype. Therefore, the present study reveals the potential mechanism of the herbal extract to prevent metabolic syndrome in rats.